Method for removing metal elements, improving paper pulp performance and reducing wastewater COD (Chemical Oxygen Demand)
By using a smaller amount of acetic acid to acid treat the pulp, the problems of low metal element removal efficiency and poor reduction of wastewater COD in the pulp are solved, and the effect of efficient removal of metal elements and reducing wastewater COD is achieved.
Patent Information
- Application Number
- CN202411964915.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to efficiently remove metal elements from pulp, and traditional acid treatment methods have problems such as large damage to fiber structure and poor reduction of wastewater COD.
Eucalyptus pulp is acid-treated with a smaller amount of acetic acid, and the H+ in the acetic acid undergoes ion exchange reaction with the metal ions in the fibers to remove metal ions and reduce wastewater COD in the process.
It realizes efficient removal of metal elements in pulp, improves pulp performance, and effectively reduces wastewater COD, reducing environmental pollution and wastewater treatment costs.
Smart Images

Figure CN119507245A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of pulping, papermaking and wastewater treatment, and particularly relates to a method for removing metal elements, improving pulp performance and reducing COD of wastewater. Background Art
[0002] The primary source of metal ions in pulp is from the raw materials themselves. Wood contains approximately 70 inorganic elements, with potassium and calcium being the most abundant. The types and amounts of metal elements vary in different parts of the wood. The Fe content in sapwood is generally lower than in heartwood, but the Ca and Mg contents in sapwood are generally higher than in heartwood. Metal ions exist in pulp primarily in adsorbed and chelated forms. The former involves metal ions adsorbed onto fibers in the form of hydroxides, while the latter involves complexation reactions between metal ions and end groups in the pulp. The main hazards of metal elements in pulp are: (1) affecting the insulation properties of paper, reducing the electrical resistance and durability of paper-based materials, and easily causing aging of paper-based materials; (2) affecting the uniformity of paper-based materials, thereby reducing the physical properties of paper; (3) metal elements will combine with the lignin phenol-type structural units remaining in the pulp to produce new color bodies, affecting the whiteness of the pulp; (4) metal elements remain in the water circulation system of the papermaking process, causing difficulties in the treatment of wastewater in the papermaking process; therefore, the removal of metal elements in pulp is necessary to improve the performance of pulp.
[0003] Existing methods for removing metal ions from slurry include chelation, neutralization, and acid treatment. Chelation involves the interaction of a chelating agent with free metal ions and unstable metal complexes in the slurry water system, forming water-soluble complexes that bury the metal ions. The complexes are then discharged with the wash water, achieving the goal of removing metal ions. However, chelating agents are expensive and pose environmental risks. Neutralization is inefficient and time-consuming.
[0004] Acid treatment is the most common method for removing metal ions from pulp. Usually, inorganic acids such as dilute hydrochloric acid and dilute sulfuric acid are used. However, the dosage of these acids is relatively high. Concentrated acid (40%-43% HCl, 67%-72% H2SO4) pretreatment belongs to homogeneous hydrolysis. Compared with dilute acid hydrolysis, its acidity is stronger and the removal effect of metal ions is better. However, concentrated acid hydrolysis has the disadvantage that, on the one hand, H + Too high a concentration will cause the cellulose macromolecules to break down, reduce their degree of polymerization, and damage the fiber properties. On the other hand, inorganic acid substances generally contain polar substances (Cl - 、SO4 2- ), which increases the loss under the action of the electric field, which is detrimental to the dielectric properties of the insulating paper. Therefore, it is necessary to find a low-cost and highly acidic organic acid to remove metal ions from the pulp through acid treatment.
[0005] Furthermore, wastewater generated during pulp processing contains substances such as hemicellulose, lignin, macromolecular carbohydrates, and unsaturated fatty acids. Direct discharge without treatment can be detrimental to the ecological environment and human health. Currently, commonly used methods for degrading COD include chemical oxidation, advanced oxidation technology, and adsorption. These methods are costly, require complex equipment, and can cause secondary pollution. Furthermore, these methods treat wastewater that has already been generated. Therefore, reducing COD in wastewater at the source remains an unresolved issue in this field.
[0006] Based on the above, how to find a method that can efficiently remove metal elements from pulp to improve pulp performance while reducing wastewater COD is an urgent problem to be solved in this field. Summary of the Invention
[0007] In response to the problems existing in the prior art, the present invention provides a method for removing metal elements, improving pulp performance and reducing wastewater COD. Specifically, a relatively mature pulping process is used to prepare eucalyptus pulp, and then the air-dried eucalyptus pulp is mixed with ultrapure water in a ratio of 1g:50mL, and the amount of acetic acid used is 0.05%-0.3% of the added ultrapure water. The eucalyptus pulp obtained after acid treatment efficiently removes metal elements in the pulp, causes less damage to the fiber structure, improves pulp performance, and can effectively reduce wastewater COD, thereby reducing environmental pollution and reducing wastewater treatment costs.
[0008] The inventors used a relatively mature pulping process to prepare eucalyptus pulp. They then subjected the pulp to varying degrees of acid treatment to investigate the effects of acid dosage, temperature, and duration on the removal efficiency of metal ions from the pulp. By optimizing these process conditions, they were able to improve pulp performance. Compared to traditional preparation processes, the present invention uses a lower amount of acetic acid for acid treatment, effectively removing metal elements from the pulp, improving pulp performance and reducing COD in wastewater.
[0009] The main inventive concepts of the present invention are as follows: During the pulp acid treatment process, as the amount of acetic acid increases, the pH change corresponding to acetic acid decreases. This is because acetic acid is a weak acid and undergoes incomplete ionization in water. Its ionization equation is as follows: , The removal of metal ions in eucalyptus pulp is mainly through the H + It undergoes a replacement reaction with the metal ions in the fiber and is dissolved and removed. Taking calcium ions as an example, the replacement reaction is as follows: , During the acid treatment of eucalyptus pulp with acetic acid to remove metal ions, H + The removal of the overall metal ion content is mainly based on H+ An ion exchange reaction occurs with adsorbed metal ions (in the form of hydroxides), converting them to ionic form and removing them from the eucalyptus pulp. A small amount of metal ions then form complexes with acetic acid, ultimately removing the metal ions. Therefore, acetic acid treatment of eucalyptus pulp primarily removes adsorbed metal ions. Since the ash contains some metal ions, the ash content decreases with the removal of these metal ions.
[0010] The reason why metal ions cannot be completely removed is that under acid treatment conditions, the metal cations adsorbed on the fiber surface undergo ion exchange with the hydrogen ions in the solution. The acidity gradually weakens during the reaction process. In order to maintain ionization balance, the metal ions that have been resolved again undergo ion exchange with the hydrogen ions at the end of the pulp fiber and are re-adsorbed on the pulp. 2+ Mg 2+ and Fe 3+ Some of the metal ions exist in the lignin units of the pulp, and the complexation reaction of acetic acid cannot completely react them out; the washing process is accompanied by an increase in pH value, which causes the dissolved but not removed metal ions to be re-adsorbed on the fiber in the form of precipitation.
[0011] The specific technical solutions of the present invention are as follows: A method for removing metal elements, improving pulp performance and reducing wastewater COD, comprising the following steps: (1) Eucalyptus chips of uniform quality were subjected to sulfate cooking. The amount of alkali used in cooking was 21% (relative to the mass fraction of absolute dry pulp), the liquid ratio was 5:1, the sulfidation degree was 25%, the heating time was 90 min, the holding time was 60 min, and the maximum temperature was 165 °C. The cooked eucalyptus pulp was rinsed with ultrapure water and then air-dried. The air-dried eucalyptus pulp was placed in a sealed bag and stored in a refrigerator for later use.
[0012] (2) taking a certain amount of the air-dried eucalyptus pulp prepared in step (1) and placing it in a ground-mouth triangular flask, adding a certain amount of ultrapure water, then adding acetic acid, adding a rotor to stir evenly, the pulp concentration is 2%, placing it in an oil bath and heating it to a certain temperature, stopping heating after reaching the specified reaction time, filtering to obtain waste water, taking out the pulp, washing it with ultrapure water until it is neutral and storing it for later use; In the above steps, air-dried eucalyptus pulp is mixed with ultrapure water in a ratio of 1g:50mL, the amount of acetic acid used is 0.05%-0.3% (volume fraction) of the added ultrapure water, the pulp concentration after adding acetic acid is 2%, the heating temperature is 50℃-90℃, and the reaction time is 20min-100min.
[0013] (3) The ash content of the untreated eucalyptus pulp and the pulp obtained in step (2) was measured using a fully automatic moisture and ash meter, and the ash removal rate was calculated.
[0014] (4) A certain amount of the pulp obtained in step (2) was taken, a certain amount of hydrochloric acid and nitric acid was added, and the mixture was digested in a hydrothermal synthesizer. The digestate was taken out and transferred to a 25 mL volumetric flask for constant volume. After the digestate was digested and filtered through a filter membrane, the metal ion content in the digestate was determined by ICP-OES using a plasma spectrometer. The metal ion content of the untreated eucalyptus pulp was detected by the same method, and the metal ion content was compared with the metal ion content after the acid decomposition. The metal ion removal effect of the eucalyptus pulp was calculated, including iron ions, calcium ions, sodium ions, and magnesium ions.
[0015] (5) Take the untreated eucalyptus pulp and the pulp obtained in step (2), and measure the kappa number using the method described in Tappi Useful Method UM 246.
[0016] (6) The untreated eucalyptus pulp and the pulp obtained in step (2) were respectively beaten and paper-made, and the beating properties of the pulp were tested, including the beating degree and whiteness of the pulp, and the properties of the paper were tested, including the tensile index, bursting index, tearing index, and folding endurance.
[0017] (7) Take the wastewater obtained after treatment in step (2) and detect the COD content of the wastewater according to the "Determination of Chemical Oxygen Demand in Water - Dichromate Method" (HJ828-2017).
[0018] In step (4), 2 mL of hydrochloric acid and 6 mL of nitric acid were added to every 0.1 g of pulp (absolutely dry), and a 0.22 μm filter membrane was used. The purpose of digesting the pulp is to dissolve the metal ions in the pulp into the digestion solution and oxidize them into high-valent metal ions to improve the accuracy of the detection.
[0019] In the step (6), the beating rotation number is 12kr.
[0020] The present invention improves the pulp acid treatment method, adopts acetic acid for acid treatment, acetic acid is incompletely ionized in water, and the H + It undergoes ion exchange reaction with the metal ions in the fiber, replacing the metal ions and reducing the ash content. The acetic acid dosage is low, further reducing the COD of the wastewater.
[0021] In summary, the present invention provides a method for removing metal elements and improving pulp performance and reducing wastewater COD. Using a small amount of acetic acid to acid-treat pulp can efficiently remove metal elements in the pulp with less damage to the fiber structure, improve pulp performance, and effectively reduce wastewater COD, thereby reducing environmental pollution and reducing wastewater treatment costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 These are SEM images of the pulp before and after metal ion removal in Example 5, where (a) is the SEM image of the original pulp, (b) is the SEM image of the pulp treated with acid at 70°C, (c) is the metal element distribution diagram of the original pulp, and (d) is the metal element distribution diagram of the pulp treated with acid at 70°C; Figure 2-Figure 6 The following are the effects of acetic acid dosage on the removal rates of ash, iron ions, calcium ions, sodium ions and magnesium ions in pulp (reaction temperature is 60℃, reaction time is 60min); Figure 7-11 The following is the effect of reaction temperature on the removal rate of ash, iron ion, calcium ion, sodium ion and magnesium ion in pulp (acetic acid dosage is 0.25%, reaction time is 60min); Figure 12-16 The following is the effect of reaction time on the removal rate of ash, iron ion, calcium ion, sodium ion and magnesium ion in pulp (acetic acid dosage is 0.25%, reaction temperature is 70℃). DETAILED DESCRIPTION
[0023] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0024] Example 1 A method for removing metal elements, improving pulp performance and reducing wastewater COD, the specific steps are as follows: (1) Eucalyptus chips of uniform quality were steamed by sulfate method. The alkali content of steaming was 21%, the pot load was 800 g (absolutely dry), the liquid ratio was 5:1, the sulfidation degree was 25%, the heating time was 90 min, the holding time was 60 min, and the maximum temperature was 165 °C. The steamed eucalyptus pulp was rinsed with ultrapure water and then air-dried. The air-dried eucalyptus pulp was placed in a sealed bag and stored in the refrigerator for later use.
[0025] (2) Take 2 g of the air-dried eucalyptus pulp prepared in step (1) and place it in a ground-mouth conical flask. Add 100 mL of ultrapure water and then add acetic acid (the acid dosage is 0.25% by volume of the added ultrapure water). Add a rotor and stir evenly. The final pulp concentration is 2%. Place it in a 60°C oil bath and heat it. After the specified reaction time of 60 min, stop heating, filter to obtain waste water, take out the pulp, wash it with ultrapure water until it is neutral, and store it for later use.
[0026] (3) The ash content of the untreated eucalyptus pulp and the pulp obtained in step (2) was measured using a fully automatic moisture and ash analyzer, and the ash removal rate was calculated to be 47.92%.
[0027] (4) Take the slurry obtained in step (2), add 2 mL of hydrochloric acid and 6 mL of nitric acid for every 0.1 g of slurry (absolutely dry), mix and enter the hydrothermal synthesizer for digestion. After the digestion solution is taken out, transfer it to a 25 mL volumetric flask and adjust the volume. After the digestion solution is filtered through a 0.22 μm filter membrane, use a plasma spectrometer to measure the metal ion content in the digestion solution; The same method was used to detect the metal ion content of eucalyptus pulp that had not been acid-treated. The metal ion content was compared with the metal ion content after the above acid hydrolysis, and the metal ion removal effect of eucalyptus pulp was calculated. The results showed that the iron ion removal rate was 38.55%, the calcium ion removal rate was 42.43%, the sodium ion removal rate was 68.65%, and the magnesium ion removal rate was 46.81%.
[0028] (5) The kappa number of the untreated eucalyptus pulp and the pulp obtained in step (2) was measured using the method described in Tappi Useful Method UM 246. The results showed that the kappa number of the pulp treated with acetic acid decreased by 19.24% compared with the kappa number of the original pulp, and the viscosity decreased by 6.83%. Although the viscosity of the pulp treated with acid decreased compared with the original pulp, the decrease was relatively small.
[0029] (6) The untreated eucalyptus pulp and the pulp obtained in step (2) were respectively beaten and paper-made, and the beating performance of the pulp and the paper properties were tested. The results showed that when the beating speed was 12 kr, the beating degree of the pulp after acetic acid treatment decreased by 14.17%, the pulp brightness increased by 8.75%, the tensile index of the paper increased by 12.26%, the burst index of the paper increased by 23.67%, the tear index of the paper decreased by 18.74%, and the folding endurance of the paper decreased by 48.05%.
[0030] (7) The wastewater obtained after treatment in step (2) was tested for COD content according to the "Determination of Chemical Oxygen Demand in Water - Dichromate Method" (HJ828-2017). Compared with the COD value of the wastewater discharge standard, the COD in the wastewater after acetic acid treatment was reduced by 24.61%.
[0031] Example 2 A method for removing metal elements, improving pulp performance and reducing wastewater COD, the specific steps are as follows: (1) The preparation method of air-dried eucalyptus pulp is the same as step (1) of Example 1.
[0032] (2) Take 2 g of the air-dried eucalyptus pulp prepared in step (1) and place it in a ground-mouth conical flask, add 100 mL of ultrapure water, and then add a certain amount of acetic acid solution (the acid dosage is 0.20% by volume of the added ultrapure water), add a rotor to stir evenly, the pulp concentration is 2%, place it in a 60°C oil bath pot and heat it. After reaching the specified reaction time of 60 min, stop heating, filter to obtain wastewater, take out the pulp, wash it with ultrapure water until it is neutral and store it for later use.
[0033] (3) The ash content of the untreated eucalyptus pulp and the pulp obtained in step (2) was measured using a fully automatic moisture and ash analyzer, and the ash removal rate was calculated to be 45.11%.
[0034] (4) Take the slurry obtained in step (2), add 2 mL of hydrochloric acid and 6 mL of nitric acid to every 0.1 g of slurry (absolutely dry), mix and then enter the hydrothermal synthesizer for digestion. After the digestion solution is taken out, transfer it to a 25 mL volumetric flask and adjust the volume. After the digestion solution is filtered through a 0.22 μm filter membrane, use a plasma spectrometer to measure the metal ion content in the digestion solution; The same method was used to detect the metal ion content of eucalyptus pulp that had not been acid-treated. The metal ion content was compared with the metal ion content after the above acid hydrolysis, and the metal ion removal effect of eucalyptus pulp was calculated. The results showed that the iron ion removal rate was 37.26%, the calcium ion removal rate was 36.53%, the sodium ion removal rate was 66.13%, and the magnesium ion removal rate was 36.32%.
[0035] (5) The kappa number of the untreated eucalyptus pulp and the pulp obtained in step (2) was measured using the method described in Tappi Useful Method UM 246. The results showed that the kappa number of the pulp treated with acetic acid decreased by 17.38% compared with the kappa number of the original pulp, and the viscosity decreased by 4.16%. Although the viscosity of the pulp treated with acid decreased compared with the original pulp, the decrease was relatively small.
[0036] (6) The untreated eucalyptus pulp and the pulp obtained in step (2) were respectively beaten and paper-made, and the beating performance of the pulp and the paper properties were tested. The results showed that when the beating speed was 12 kr, the beating degree of the pulp after acetic acid treatment decreased by 11.81%, the pulp brightness increased by 7.21%, the tensile index of the paper increased by 10.13%, the burst index of the paper increased by 19.82%, the tear index of the paper decreased by 16.22%, and the folding endurance of the paper decreased by 45.52%.
[0037] (7) The wastewater obtained after treatment in step (2) was tested for COD content according to the "Determination of Chemical Oxygen Demand in Water - Dichromate Method" (HJ828-2017). Compared with the COD value of the wastewater discharge standard, the COD in the wastewater after treatment with acetic acid was reduced by 22.67%.
[0038] Example 3 A method for removing metal elements, improving pulp performance and reducing wastewater COD, the specific steps are as follows: (1) The preparation method of air-dried eucalyptus pulp is the same as step (1) of Example 1.
[0039] (2) Take 2 g of the air-dried eucalyptus pulp prepared in step (1) and place it in a ground-mouth conical flask. Add 100 mL of ultrapure water and then add a certain amount of acetic acid solution (the acid dosage is 0.25% by volume of the added ultrapure water). Add a rotor and stir evenly. The pulp concentration is 2%. Place it in a 70°C oil bath and heat it. After reaching the specified reaction time of 60 min, stop heating, filter to obtain wastewater, take out the pulp, wash it with ultrapure water until it is neutral, and store it for later use.
[0040] (3) The ash content of the untreated eucalyptus pulp and the pulp obtained in step (2) was measured using a fully automatic moisture and ash analyzer, and the ash removal rate was calculated to be 57.73%.
[0041] (4) Take the slurry obtained in step (2), add 2 mL of hydrochloric acid and 6 mL of nitric acid to every 0.1 g of slurry (absolutely dry), mix and then enter the hydrothermal synthesizer for digestion. After the digestion solution is taken out, transfer it to a 25 mL volumetric flask and adjust the volume. After the digestion solution is filtered through a 0.22 μm filter membrane, use a plasma spectrometer to measure the metal ion content in the digestion solution; The same method was used to detect the metal ion content of eucalyptus pulp that had not been acid-treated. The metal ion content was compared with the metal ion content after the above acid hydrolysis, and the metal ion removal effect of eucalyptus pulp was calculated. The results showed that the iron ion removal rate was 48.95%, the calcium ion removal rate was 52.26%, the sodium ion removal rate was 70.08%, and the magnesium ion removal rate was 56.63%.
[0042] (5) The kappa number of the untreated eucalyptus pulp and the pulp obtained in step (2) was measured using the method described in Tappi Useful Method UM 246. The results showed that the kappa number of the pulp treated with acetic acid decreased by 24.37% compared with the kappa number of the original pulp, and the viscosity decreased by 8.58%. The viscosity of the pulp treated with acid decreased compared with the original pulp.
[0043] (6) The untreated eucalyptus pulp and the pulp obtained in step (2) were respectively beaten and paper-made, and the beating performance of the pulp and the paper properties were tested. The results showed that when the beating speed was 12 kr, the beating degree of the pulp after acetic acid treatment decreased by 14.75%, the pulp brightness increased by 12.06%, the tensile index of the paper increased by 16.39%, the burst index of the paper increased by 29.02%, the tear index of the paper decreased by 21.84%, and the folding endurance of the paper decreased by 51.28%.
[0044] (7) The wastewater obtained after treatment in step (2) was tested for COD content according to the "Determination of Chemical Oxygen Demand in Water - Dichromate Method" (HJ828-2017). Compared with the COD value of the wastewater discharge standard, the COD in the wastewater after treatment with acetic acid was reduced by 26.12%.
[0045] Example 4 A method for removing metal elements, improving pulp performance and reducing wastewater COD, the specific steps are as follows: (1) The preparation method of air-dried eucalyptus pulp is the same as step (1) of Example 1.
[0046] (2) Take 2 g of the air-dried eucalyptus pulp prepared in step (1) and place it in a ground-mouth conical flask. Add 100 mL of ultrapure water and then add a certain amount of acetic acid solution (the acid dosage is 0.25% by volume of the added ultrapure water). Add a rotor and stir evenly. The pulp concentration is 2%. Place it in an 80°C oil bath and heat it. After reaching the specified reaction time of 60 min, stop heating, filter to obtain wastewater, take out the pulp, wash it with ultrapure water until it is neutral, and store it for later use.
[0047] (3) The ash content of the untreated eucalyptus pulp and the pulp obtained in step (2) was measured using a fully automatic moisture and ash analyzer, and the ash removal rate was calculated to be 58.12%.
[0048] (4) Take the slurry obtained in step (2), add 2 mL of hydrochloric acid and 6 mL of nitric acid to every 0.1 g of slurry (absolutely dry), mix and then enter the hydrothermal synthesizer for digestion. After the digestion solution is taken out, transfer it to a 25 mL volumetric flask and adjust the volume. After the digestion solution is filtered through a 0.22 μm filter membrane, use a plasma spectrometer to measure the metal ion content in the digestion solution; The same method was used to detect the metal ion content of eucalyptus pulp that had not been acid-treated. The metal ion content was compared with the metal ion content after the above acid hydrolysis, and the metal ion removal effect of eucalyptus pulp was calculated. The results showed that the iron ion removal rate was 49.06%, the calcium ion removal rate was 52.88%, the sodium ion removal rate was 71.74%, and the magnesium ion removal rate was 57.58%.
[0049] (5) The kappa number of the untreated eucalyptus pulp and the pulp obtained in step (2) was measured using the method described in Tappi Useful Method UM 246. The results showed that the kappa number of the pulp treated with acetic acid decreased by 25.01% compared with the kappa number of the original pulp, and the viscosity decreased by 9.16%. The viscosity of the pulp treated with acid decreased compared with the original pulp.
[0050] (6) The untreated eucalyptus pulp and the pulp obtained in step (2) were respectively beaten and paper-made, and the beating performance of the pulp and the paper properties were tested. The results showed that when the beating speed was 12 kr, the beating degree of the pulp after acetic acid treatment decreased by 15.14%, the pulp brightness increased by 14.25%, the tensile index of the paper increased by 18.36%, the burst index of the paper increased by 31.67%, the tear index of the paper decreased by 23.30%, and the folding endurance of the paper decreased by 54.82%.
[0051] (7) The wastewater obtained after treatment in step (2) was tested for COD content according to the "Determination of Chemical Oxygen Demand in Water - Dichromate Method" (HJ828-2017). Compared with the COD value of the wastewater discharge standard, the COD in the wastewater after treatment with acetic acid was reduced by 30.77%.
[0052] Example 5 A method for removing metal elements, improving pulp performance and reducing wastewater COD, the specific steps are as follows: (1) The preparation method of air-dried eucalyptus pulp is the same as step (1) of Example 1.
[0053] (2) Take 2 g of the air-dried eucalyptus pulp prepared in step (1) and place it in a ground-mouth triangular flask. Add 100 mL of ultrapure water and then add a certain amount of acetic acid solution (the acid dosage is 0.25% by volume of the added ultrapure water). Add a rotor and stir evenly. The pulp concentration is 2%. Place it in a 70°C oil bath and heat it. After the specified reaction time of 80 min, stop heating, filter to obtain waste water, take out the pulp, wash it with ultrapure water until it is neutral, and store it for later use.
[0054] (3) The ash content of the untreated eucalyptus pulp and the pulp obtained in step (2) was measured using a fully automatic moisture and ash analyzer, and the ash removal rate was calculated to be 66.80%.
[0055] (4) Take the slurry obtained in step (2), add 2 mL of hydrochloric acid and 6 mL of nitric acid to every 0.1 g of slurry (absolutely dry), mix and then enter the hydrothermal synthesizer for digestion. After the digestion solution is taken out, transfer it to a 25 mL volumetric flask and adjust the volume. After the digestion solution is filtered through a 0.22 μm filter membrane, use a plasma spectrometer to measure the metal ion content in the digestion solution; The same method was used to detect the metal ion content of eucalyptus pulp that had not been acid-treated. The metal ion content was compared with the metal ion content after the above acid hydrolysis, and the metal ion removal effect of eucalyptus pulp was calculated. The results showed that the iron ion removal rate was 52.75%, the calcium ion removal rate was 57.72%, the sodium ion removal rate was 68.45%, and the magnesium ion removal rate was 57.36%.
[0056] (5) The kappa number of the untreated eucalyptus pulp and the pulp obtained in step (2) was measured using the method described in Tappi Useful Method UM 246. The results showed that the kappa number of the pulp treated with acetic acid decreased by 25.28% compared with the kappa number of the original pulp, and the viscosity decreased by 10.73%. The viscosity of the pulp treated with acid decreased compared with the original pulp.
[0057] (6) The untreated eucalyptus pulp and the pulp obtained in step (2) were respectively beaten and paper-made, and the beating performance of the pulp and the paper properties were tested. The results showed that when the beating speed was 12 kr, the beating degree of the pulp after acetic acid treatment decreased by 16.40%, the pulp brightness increased by 15.18%, the tensile index of the paper increased by 21.85%, the burst index of the paper increased by 32.82%, the tear index of the paper decreased by 23.69%, and the folding endurance of the paper decreased by 53.51%.
[0058] (7) The wastewater obtained after treatment in step (2) was tested for COD content according to the "Determination of Chemical Oxygen Demand in Water - Dichromate Method" (HJ828-2017). Compared with the COD value of the wastewater discharge standard, the COD in the wastewater after treatment with acetic acid was reduced by 28.00%.
[0059] Example 6 A method for removing metal elements, improving pulp performance and reducing wastewater COD, the specific steps are as follows: (1) The preparation method of air-dried eucalyptus pulp is the same as step (1) of Example 1.
[0060] (2) Take 2 g of the air-dried eucalyptus pulp prepared in step (1) and place it in a ground-mouth triangular flask, add 100 mL of ultrapure water, and then add a certain amount of acetic acid solution (the acid dosage is 0.25% by volume of the added ultrapure water), add a rotor to stir evenly, the pulp concentration is 2%, place it in a 70°C oil bath and heat it. After reaching the specified reaction time of 100 min, stop heating, filter to obtain wastewater, take out the pulp, wash it with ultrapure water until it is neutral, and store it for later use.
[0061] (3) The ash content of the untreated eucalyptus pulp and the pulp obtained in step (2) was measured using a fully automatic moisture and ash analyzer, and the ash removal rate was calculated to be 65.02%.
[0062] (4) Take the slurry obtained in step (2), add 2 mL of hydrochloric acid and 6 mL of nitric acid to every 0.1 g of slurry (absolutely dry), mix and then enter the hydrothermal synthesizer for digestion. After the digestion solution is taken out, transfer it to a 25 mL volumetric flask and adjust the volume. After the digestion solution is filtered through a 0.22 μm filter membrane, use a plasma spectrometer to measure the metal ion content in the digestion solution; The same method was used to detect the metal ion content of eucalyptus pulp that had not been acid-treated. The metal ion content was compared with the metal ion content after the above acid hydrolysis, and the metal ion removal effect of eucalyptus pulp was calculated. The results showed that the iron ion removal rate was 54.74%, the calcium ion removal rate was 58.16%, the sodium ion removal rate was 74.07%, and the magnesium ion removal rate was 60.22%.
[0063] (5) The kappa number of the untreated eucalyptus pulp and the pulp obtained in step (2) was measured using the method described in Tappi Useful Method UM 246. The results showed that the kappa number of the pulp treated with acetic acid decreased by 25.92% compared with the kappa number of the original pulp, and the viscosity decreased by 12.87%. The viscosity of the pulp treated with acid decreased compared with the original pulp.
[0064] (6) The untreated eucalyptus pulp and the pulp obtained in step (2) were respectively beaten and paper-made, and the beating performance of the pulp and the paper properties were tested. The results showed that when the beating speed was 12 kr, the beating degree of the pulp after acetic acid treatment decreased by 17.02%, the pulp brightness increased by 15.87%, the tensile index of the paper increased by 23.16%, the burst index of the paper increased by 33.54%, the tear index of the paper decreased by 24.54%, and the folding endurance of the paper decreased by 56.20%.
[0065] (7) The wastewater obtained after treatment in step (2) was tested for COD content according to the "Determination of Chemical Oxygen Demand in Water - Dichromate Method" (HJ828-2017). Compared with the COD value of the wastewater discharge standard, the COD in the wastewater after treatment with acetic acid was reduced by 30.86%.
[0066] In the comparative example, citric acid was used to treat the pulp, and the specific implementation process was as follows: (1) The preparation method of air-dried eucalyptus pulp is the same as step (1) of Example 1.
[0067] (2) Take 2 g of the air-dried eucalyptus pulp prepared in step (1) and place it in a ground-mouth triangular flask. Add 100 mL of ultrapure water and then add a certain amount of citric acid solution (the acid dosage is 1% by volume of the added ultrapure water). Add a rotor and stir evenly. The pulp concentration is 2%. Place it in a 70°C oil bath and heat it. After the specified reaction time of 80 min, stop heating, filter to obtain waste water, take out the pulp, wash it with ultrapure water until it is neutral, and store it for later use.
[0068] (3) The ash content of the untreated eucalyptus pulp and the pulp obtained in step (2) was measured using a fully automatic moisture and ash analyzer, and the ash removal rate was calculated to be 60.14%.
[0069] (4) Take the slurry obtained in step (2), add 2 mL of hydrochloric acid and 6 mL of nitric acid to every 0.1 g of slurry (absolutely dry), mix and then enter the hydrothermal synthesizer for digestion. After the digestion solution is taken out, transfer it to a 25 mL volumetric flask and adjust the volume. After the digestion solution is filtered through a 0.22 μm filter membrane, use a plasma spectrometer to measure the metal ion content in the digestion solution; The same method was used to detect the metal ion content of eucalyptus pulp that had not been acid-treated. The metal ion content was compared with the metal ion content after the above acid hydrolysis, and the metal ion removal effect of eucalyptus pulp was calculated. The results showed that the iron ion removal rate was 52.35%, the calcium ion removal rate was 50.77%, the sodium ion removal rate was 75.69%, and the magnesium ion removal rate was 51.54%.
[0070] (5) The kappa number of the untreated eucalyptus pulp and the pulp obtained in step (2) was measured using the method described in Tappi Useful Method UM 246. The results showed that the kappa number of the pulp treated with citric acid decreased by 20.63% compared with the kappa number of the original pulp, and the viscosity decreased by 11.58%. The viscosity of the pulp treated with acid decreased compared with the original pulp.
[0071] (6) The untreated eucalyptus pulp and the pulp obtained in step (2) were respectively beaten and paper-made, and the beating performance of the pulp and the paper properties were tested. The results showed that when the beating speed was 12 kr, the beating degree of the pulp after citric acid treatment decreased by 14.07%, the pulp brightness increased by 10.92%, the tensile index of the paper increased by 15.42%, the burst index of the paper increased by 21.66%, the tear index of the paper decreased by 20.14%, and the folding endurance of the paper decreased by 56.81%.
[0072] (7) The wastewater obtained after treatment in step (2) was tested for COD content according to the "Determination of Chemical Oxygen Demand in Water - Dichromate Method" (HJ828-2017). Compared with the COD value of the wastewater discharge standard, the COD in the wastewater after citric acid treatment was reduced by 20.26%.
[0073] Experimental example The comparison of the test results of Example 5 and the comparative example is shown in Table 1. By comparison, it can be seen that in the present invention, acetic acid is used to treat the pulp for acid treatment. Compared with the treatment with citric acid, the acetic acid treatment can achieve a metal ion removal efficiency equivalent to that of the citric acid treatment with a lower acid dosage. Among them, the removal rates of calcium ions and magnesium ions are significantly improved, and the pulp ash removal rate and the Kappa number reduction effect are also improved to a certain extent. In terms of paper performance, the whiteness improvement effect, the tensile index improvement effect, the bursting index improvement effect and the folding endurance reduction effect are improved to a certain extent, and the wastewater COD reduction effect is obvious.
[0074] Table 1 Comparison of the treatment results of the comparative example and Example 5 Detection indicators Comparative Example 1 Example 5 Ash removal rate (%) 60.14 66.80 Iron ion removal rate (%) 52.35 52.75 Calcium ion removal rate (%) 50.77 57.72 Sodium ion removal rate (%) 75.69 68.45 Magnesium ion removal rate (%) 51.54 57.36 Kappa number reduction (%) 20.63 25.28 Viscosity reduction (%) 11.58 10.73 Beating degree reduction (%) 14.07 16.40 Whiteness improvement (%) 10.92 15.18 Increase in tensile index (%) 15.42 21.85 Increase in burst resistance index (%) 21.66 32.82 Tear index reduction (%) 20.14 23.69 Folding endurance reduction (%) 56.81 53.51 Wastewater COD reduction (%) 20.26 28.00 .
[0075] Performance testing The eucalyptus pulp in Example 5 and the pulp after acid treatment in step (2) were respectively tested for metal element content and ash content. The test results are shown in Table 2.
[0076] Table 2 Metal element content and ash content of eucalyptus pulp and acetic acid treated pulp sample <![CDATA[Iron ion content (mg·Kg -1 )]]> <![CDATA[Calcium ion content (mg·Kg -1 )]]> <![CDATA[Sodium ion content (mg·Kg -1 )]]> <![CDATA[Magnesium ion content (mg·Kg -1 )]]> Ash content (%) Eucalyptus pulp 32.70 2683.46 402.55 265.99 41.32 After acetic acid treatment 15.45 1134.57 127.00 113.42 13.72 As can be seen from Table 2, after the eucalyptus pulp was treated with acetic acid, the iron ion, calcium ion, sodium ion and magnesium ion contents in the pulp were effectively reduced, and the ash removal effect was also significant.
[0077] Figure 1 These are SEM images of the pulp in Example 5 before and after metal ion removal. (a) is the SEM image of the original pulp, (b) is the SEM image of the pulp treated with acid at 70°C, (c) is the metal element distribution of the original pulp, and (d) is the metal element distribution of the pulp treated with acid at 70°C. The images show that the cellulose structure is intact after acetic acid treatment, and the interfiber spaces are larger. This indicates that removing metal ions from the pulp with acetic acid under low-acid and low-temperature conditions does not disrupt the fiber structure but reduces the connections between fibers. (c) and (d) are the distribution diagrams of Na, Mg, Ca, and Fe for the original pulp and the pulp treated with acetic acid, respectively. The fluorescence intensity of each metal element in the eucalyptus pulp after acid treatment is lower than that in the original pulp. Therefore, acid treatment with acetic acid is significantly effective in removing metal ions from pulp, while causing minimal damage to the fiber structure.
[0078] Taking Example 1 and Example 2 as examples, the effect of the amount of acetic acid used in the acid treatment was explored. Figure 2-Figure 6The following is the effect of acetic acid dosage on the removal rate of ash, iron ions, calcium ions, sodium ions and magnesium ions in pulp. It can be seen that under the conditions of reaction temperature of 60℃ and reaction time of 60min, when the acetic acid dosage increases from 0.05% to 0.2%, the removal rate of ash, iron ions, calcium ions, sodium ions and magnesium ions in pulp is significantly improved. When the acid concentration reaches 0.25%, the acid dosage continues to increase, the removal rate increases slightly and tends to be stable.
[0079] Taking Examples 3 and 4 as examples, the effect of reaction temperature during acid treatment was explored. Figure 7-11 The following is the effect of reaction temperature on the removal rate of ash, iron ions, calcium ions, sodium ions and magnesium ions in pulp. It can be seen that under the conditions of acetic acid dosage of 0.25% and reaction time of 60min, when the reaction temperature is increased from 50℃ to 70℃, the removal rate of ash, iron ions, calcium ions, sodium ions and magnesium ions in pulp is significantly improved. When the temperature reaches 70℃, the removal rate increases slightly and tends to be stable if the temperature is continued to be increased.
[0080] Taking Examples 5 and 6 as examples, the effect of reaction time in acid treatment was explored. Figure 12-16 The following is the effect of reaction time on the removal rate of ash, iron ions, calcium ions, sodium ions and magnesium ions in pulp. It can be seen that under the conditions of acetic acid dosage of 0.25% and reaction temperature of 70℃, when the reaction time increases from 20min to 80min, the removal rate of ash, iron ions, calcium ions, sodium ions and magnesium ions in pulp is significantly improved. As the reaction time continues to increase, the removal rate increases slightly and tends to be stable.
[0081] Therefore, the acid treatment method provided by the present invention can achieve the effect of efficiently removing metal elements in pulp with a smaller amount of acetic acid, thereby improving pulp performance, reducing industrial costs, and effectively reducing wastewater COD, thereby reducing pollution and treatment costs.
[0082] The above embodiments enable one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be readily apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is not limited to the embodiments shown herein but is to be construed in the widest possible manner consistent with the principles and novel features disclosed herein.
Claims
1. A method for removing metal elements and improving pulp performance and reducing wastewater COD, characterized in that: The specific steps are as follows: (1) taking eucalyptus chips of uniform quality and performing kraft cooking, the cooked eucalyptus pulp is rinsed with ultrapure water and then air-dried, and the air-dried eucalyptus pulp is put into a sealed bag and stored in a refrigerator for later use; (2) A certain amount of the air-dried eucalyptus pulp prepared in step (1) is placed in a ground-mouth conical flask, a certain amount of ultrapure water is added, and then acetic acid is added. A rotor is added to stir evenly. The pulp concentration is 2%. The pulp is placed in an oil bath and heated to a certain temperature. After the specified reaction time is reached, the heating is stopped, and the waste water is filtered out. The pulp is taken out and washed with ultrapure water until it is neutral and stored for later use.
2. The method for removing metal elements and improving pulp performance and reducing wastewater COD according to claim 1, characterized in that: In step (1), the amount of alkali used in the sulfate cooking is 21%, the liquid-to-liquid ratio is 5:1, the sulfidation degree is 25%, the heating time is 90 minutes, the heat preservation time is 60 minutes, and the maximum temperature is 165°C.
3. The method for removing metal elements and improving pulp performance and reducing wastewater COD according to claim 1, characterized in that: In step (2), air-dried eucalyptus pulp is mixed with ultrapure water in a ratio of 1 g:50 mL, the amount of acid used is 0.05%-0.3% of the volume of ultrapure water added, the pulp concentration after adding acetic acid is 2%, the heating temperature is 50°C-90°C, and the reaction time is 20min-100min.
4. The method for removing metal elements and improving pulp performance and reducing wastewater COD according to claim 1, characterized in that: The slurry obtained in step (2) is tested for ash content using a fully automatic moisture ash tester, and the ash removal rate is calculated.
5. The method for removing metal elements and improving pulp performance and reducing wastewater COD according to claim 1, characterized in that: Take the slurry obtained in step (2), add a certain amount of hydrochloric acid and nitric acid, mix and enter the hydrothermal synthesizer for digestion, take out the digestion solution and transfer it to a 25mL volumetric flask for constant volume, filter the digestion solution through a filter membrane, and use a plasma spectrometer to measure the metal ion content in the digestion solution by ICP-OES, and calculate the metal ion removal effect of eucalyptus pulp.
6. The method for removing metal elements and improving pulp performance and reducing wastewater COD according to claim 5, characterized in that: For every 0.1 g of absolute dry slurry, add 2 mL of hydrochloric acid and 6 mL of nitric acid, and use a 0.22 micron filter membrane.
7. The method for removing metal elements and improving pulp performance and reducing wastewater COD according to claim 5, characterized in that: The metal ions include iron ions, calcium ions, sodium ions and magnesium ions.
8. The method for removing metal elements and improving pulp performance and reducing wastewater COD according to claim 1, characterized in that: The pulp obtained in step (2) was used for pulping and papermaking, and the pulping performance and paper performance of the pulp were tested, wherein the pulping rotation number was 12 kr.